POLITENESS IN THE CONTEXT OF SOCIAL INEQUALITY: A CASE STUDY OF THE MOVIE 'CRAZY RICH ASIANS' - Khodijah, Siti; Hayuningtyas, Nina; Degaf, Agwin (Annual International Conferences on Language, Literature, and Media, 2023)
The primary objective of this research is to explore the specific politeness strategies employed by the characters in the movie "Crazy Rich Asians." The film portrays various conflicts revolving around discrimination, social inequality, prejudice, and racial issues. Throughout the movie, the characters express themselves using words, phrases, or sentences that reflect the existing social imbalances influenced by their respective social statuses. This qualitative descriptive study aims to gain a comprehensive understanding and interpretation of how politeness is employed by the characters in their dialogues. The research process involves analyzing the data, displaying the collected information, reducing it to manageable segments, interpreting the underlying patterns, and drawing meaningful conclusions from the findings. The research findings reveal that the majority of the characters in the movie predominantly adopt a bold on-record strategy when communicating, primarily due to the prominent themes of minority and majority classes. As a result, the dialogues and interactions of these characters may evoke discomfort or unease among the audience. In summary, this study provides valuable insights into the politeness strategies employed by the characters in the movie "Crazy Rich Asians," highlighting the complexities and dynamics of communication in the context of discrimination, social inequality, prejudice, and race.